To find the mirror image of the y-intercept of the function \( y = -x^2 - x + 2 \), we first need to determine the y-intercept itself. The y-intercept is found by setting \( x = 0 \).
Calculating \( y \) when \( x = 0 \):
\[ y = -0^2 - 0 + 2 = 2 \]
So, the y-intercept is at the point \( (0, 2) \).
The mirror image of a point with respect to the y-axis can be found by negating the x-coordinate while keeping the y-coordinate the same. Therefore, the mirror image of the y-intercept \( (0, 2) \) is:
\[ (0, 2) \rightarrow (0, 2) \]
Thus, the correct answer is:
\((0, 2)\)